PENGARUH PAJAK, PROFITABILITAS, DEBT COVENANT, DAN GOOD CORPORATE GOVERNANCE TERHADAP TRANSFER PRICING PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Fernanda, Armilia; Wahyuningsih , Eny; Diana, Haugesti (Journal Of Islamic Finance And Accounting Research, 2023)
This study aims to determine the effect of tax, profitability, debt covenants, and good corporate governance on transfer pricing in manufacturing companies in various industrial sectors listed on the IDX in 2018-2021. This research is a descriptive research with a quantitative approach. The type of data collected is secondary data. The total population used is all manufacturing companies in the various industrial sectors listed on the IDX for 2018-2021, totaling 55 companies with a total sample of 11 companies obtained using the purposive sampling method. The method used in this study consisted of descriptive statistical tests, classical assumption tests, multiple regression analysis, and hypothesis testing with the help of the SPSS version 23 program. The results of this study indicate that testing with the partial test (t test) shows that the variables tax, profitability, and debt covenants have no significant effect on transfer pricing. Meanwhile, the good corporate governance variable has a negative and significant effect on transfer pricing. The ANOVA test (F test) shows that the variables of tax, profitability, debt covenants, and good corporate governance have a significant influence on transfer pricing together. The independent variable explaining the effect of transfer pricing is 10.4% while the remaining 89.6% is influenced by other variables not examined in this study. Such as tunneling incentive variables, bonus mechanisms, foreign ownership, company size, leverage, and intangible assets.